Corrigendum: Efficacy and safety of travoprost alone or in combination with other agents for glaucoma and ocular hypertension: patient considerations - Suzuki CLB (Dove Medical Press, 2010)
Suzuki Er, Suzuki CLBCorrected textTwo paragraphs on page 1168 of Suzuki & Suzuki were not cited correctly.The data presented in the first paragraph should have been cited with reference number 35 and the following paragraph with a new reference, number 36. All subsequent references and citations were renumbered by one.